Nidificación del Atajacaminos Oscuro (Caprimulgus sericocaudatus) en Misiones, Argentina - Chebez, Juan Carlos (1988)
The finding of a nest of the Silky-tailed Nightjarin the Urugua-íbasin, Misiones, is commented. The clutch consisted of 2 eggs laid in the forest litter. W. Partridge collected in 1957 two nestlings of the species in the same area.